Articulating childhood trauma: In the context of war, sexual abuse and disability - Kumar, Kamayani (Routledge, Taylor & Francis Group, 2024)
"The volume addresses pertinent need to examine childhood trauma revolved around nuanced themes of war, sexual abuse, and disability. Drawing narratives from spatial, temporal, and cultural contexts, the book analyses how conflict, abuse, domestic violence, contours of gender construction, and narratives of ableism affect a child's transactions with society. While exploring complex manifestations of children's experience of trauma, the volume seeks to understand the issues related to translatability, or representation, of trauma bearing in mind the fact that children often lack the language to express their sense of loss. The book in its study of select literary pieces, uses drawings, memoirs, and graphic narratives in the process. Academicians and research scholars from the disciplines of childhood studies, trauma studies, resilience Studies, visual studies, gender studies, cultural studies, disability studies, and film studies stand to benefit from this volume. The ideas that have been found in this volume will become the focal point for further research and scholarship"--